General healthcare preferences for people aged 50 and over in England: English longitudinal study of ageing - Nicholas Steel; Paola Zaninotto; Oby O. Enwo; James Banks (PLoS ONE, 2026)
Background Treatment outcomes and satisfaction improve when healthcare decisions align with patient preferences. However, little is known about general health preferences in older adults, and eliciting patient preferences is time consuming. Aim To describe the distribution of preferences for healthcare in general, and associations between preferences and patient characteristics in adults aged 50 years and over in England. Design and setting Data were collected in wave 8 (2016/2017) of the English Longitudinal Study of Ageing (ELSA), a biennial longitudinal survey of people aged 50 and over living in private households in England that began in 2002/2003 and is designed to be nationally representative. Method Data were collected from ELSA participants using face-to-face interviews and a short self completion questionnaire. Amongst other items, the questionnaire contained six measures of general healthcare preferences that had not been asked in previous ELSA waves: risk aversion, future orientation, quality or length of life, body function compared to looks, openness to experimental treatments, and preference to leave treatment decisions to a doctor. Results Healthcare preferences varied substantially, with some systematic patterns by age and sex: women were less likely than men to want to delegate decisions to doctors, and more likely to prioritise quality of life over length of life; participants aged over 75 years were more likely than younger participants to want to delegate decisions to doctors, and more likely to want to avoid risks. Conclusion The systematic sex and age differences offer a useful starting point for eliciting healthcare preferences in a busy clinical environment, but cannot replace asking about individual preferences.